2023
DOI: 10.1002/smll.202307993
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Polythiophene Blending Strategy to Reduce the Efficiency‐Stability‐Cost Gap of Solar Cells

Qingchun Qi,
Jingjing Wang,
Mengyuan Gao
et al.

Abstract: Benefiting from the photovoltaic material innovation and delicate device optimization, high‐efficiency solar cells employing polymeric materials are thriving. Reducing the gap of cost, efficiency, and stability is the critical challenge faced by the emerging solar cells such as organics, quantum dots and perovskites. Poly(3‐alkylthiophene) demonstrates great potential in organic solar cells and quantum dot solar cells as the active layer or the hole transport layer due to its large scalability, excellent photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For QD optoelectronic devices, substantial donor polymers can be employed for hole transport, e.g., polythiophenes and other conjugated polymers. It is well established that the classical polythiophene material, P3HT, generally presents strong molecular aggregation and edge-on stacking, which result in unfavorable hole transport and an inferior optoelectronic performance. Moreover, the high energy landscape of P3HT also leads to a mismatch with PbS QDs, which places great restrictions on the further performance enhancement of QD/P3HT solar cells. , In order to tackle these concerns, our group has developed various strategies to modulate the molecular aggregation and energy landscape of polythiophenes for QD photovoltaic and photodetection devices. ,, Our group recently reported that o -xylene-processed P3HT presents moderate morphology and characteristic lengths, resulting in an increasing PCE to ∼8.7% for QD solar cells . In addition, our most recent study demonstrated that poly(3-pentylthiophene) (P3PT) could achieve decreased molecular aggregation and advantageous face-on orientation (Figure c–e), enabling a remarkable PCE enhancement of QD devices and perovskite-based devices from ∼8.6% to ∼9.5% and from ∼16% to ∼18.8%, respectively.…”
Section: Tuning the Microstructure Of Neat Conjugated Polymersmentioning
confidence: 99%
See 4 more Smart Citations
“…For QD optoelectronic devices, substantial donor polymers can be employed for hole transport, e.g., polythiophenes and other conjugated polymers. It is well established that the classical polythiophene material, P3HT, generally presents strong molecular aggregation and edge-on stacking, which result in unfavorable hole transport and an inferior optoelectronic performance. Moreover, the high energy landscape of P3HT also leads to a mismatch with PbS QDs, which places great restrictions on the further performance enhancement of QD/P3HT solar cells. , In order to tackle these concerns, our group has developed various strategies to modulate the molecular aggregation and energy landscape of polythiophenes for QD photovoltaic and photodetection devices. ,, Our group recently reported that o -xylene-processed P3HT presents moderate morphology and characteristic lengths, resulting in an increasing PCE to ∼8.7% for QD solar cells . In addition, our most recent study demonstrated that poly(3-pentylthiophene) (P3PT) could achieve decreased molecular aggregation and advantageous face-on orientation (Figure c–e), enabling a remarkable PCE enhancement of QD devices and perovskite-based devices from ∼8.6% to ∼9.5% and from ∼16% to ∼18.8%, respectively.…”
Section: Tuning the Microstructure Of Neat Conjugated Polymersmentioning
confidence: 99%
“…Inspired by the success of dual polymer blending in donor–acceptor (D–A) conjugated polymers, our group further developed the blending HTLs based on P3HT-Br and P3HT and realized a high efficiency of 11% (Figure e–g) . A very recent work by Qi et al reported another case of dual-polythiophene blending based on two simple polythiophenes (P3HT and P3PT) . Specifically, two simple polythiophenes (P3HT and P3PT) with distinct solution aggregation features (as reflected in their persistence lengths) were blended to tune the film microstructure.…”
Section: Tuning the Microstructure Of Polymer Blendsmentioning
confidence: 99%
See 3 more Smart Citations